Can habitat modification in the native range promote invasion? - Arnaud Estoup; Philip E. Hulme; Kathryn A. Hodgins; Mathieu Gautier; Eric Lombaert; Manpreet K. Dhami; Angela McGaughran; Ruth A. Hufbauer (Trends in Ecology & Evolution, 2026)

Stormwater sediment composition: bio-physico-chemical signature of organic-rich sediments and practical implications - Chabert Milèna; Tedoldi Damien; Zhan Qiufang; Gautier Mathieu; Fardel Alexandre; Lakel Abdelkader; Lipeme Kouyi Gislain; Chatain Vincent (Journal of Soils and Sediments, 2026)

Treatment wetlands in the framework of the revised European Union Urban Wastewater Treatment Directive 2024 - Mathieu Gautier (Current Opinion in Environmental Science & Health, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Population Genomics of Incipient Allochronic Divergence in the Pine Processionary Moth - Tanguy Muller; Mathieu Gautier; Éric Lombaert; Raphaël Leblois; Laure Sauné; Manuela Branco; Carole Kerdelhué; Charles Perrier (Molecular Ecology, 2025)
Allochronic divergence is a key evolutionary mechanism that can frequently lead to incipient speciation. Although theoretical models suggest that such divergence is notably facilitated by small population size and genetic polymorphisms influencing reproductive timing, though constrained by genetic load, empirical validation remains limited. We investigated these predictions by re‐analysing a case of allochronic differentiation between two sympatric populations of pine processionary moth ( Thaumetopoea pityocampa ) in Portugal, using whole genome resequencing (IndSeq and PoolSeq) of those two populations and eight allopatric ones. We inferred the demographic history of those populations, assessed their genetic load and searched for genomic regions associated with life cycle differences. Our analyses revealed a recent split between the sympatric allochronic populations, accompanied by a strong reduction in gene flow, bottlenecks, inbreeding and accumulation of deleterious variants. Genome scans identified several loci associated with life cycle variation, including genes putatively involved in circadian rhythm regulation, predominantly located on the Z chromosome. We discuss how these empirical genomic findings support theoretical expectations that assortative mating driven by differences in reproductive timing, underpinned by polymorphisms in circadian genes, along with genetic drift and purge of genetic load at high‐impact sites, can promote the onset and persistence of allochronic divergence.

Adaptive Challenges of Past and Future Invasion of Drosophila suzukii : Insights From Novel Genomic Resources and Statistical Methods Combining Individual and Pool Sequencing Data - Louise Camus; Nicolas O. Rode; Svitlana Serga; Anne Loiseau; Xiao Chen; Carole Iampietro; Marc Kenis; William Marande; Julián Mensch; Hugues Parinello; Marija Savić Veselinović; Sophie Valière; et al. (Molecular Ecology, 2025)
Global change is accelerating biological invasions, making it crucial to understand how species adapt in new environments to improve management strategies. Genomic data provide valuable insights into adaptation through genotype‐environment association (GEA) studies, which identify genes and biological processes tied to invasion success, and through geometric genomic offset (gGO) statistics, which estimate genetic (mal)adaptation to new environments. Here, we investigate genetic adaptation in the invasive pest Drosophila suzukii using novel genomic resources and statistical methods. We use a new chromosome‐level genome assembly and data from 37 populations, combining publicly available and newly generated pooled and individual sequencing data, analysed with an enhanced version of BayPass software, tailored for such hybrid datasets. First, we identify genomic regions showing genetic differentiation between native and invasive populations. Then, using a GEA with 29 environmental covariates, we estimate the gGO between the source environments and the invaded areas, shedding light on the potential adaptive challenges D. suzukii faced during previous invasions. In addition, we estimate gGO for geographical areas not yet invaded to predict future invasion risks, and identify regions from which preadapted populations may originate. Our results reveal numerous genomic regions associated with the invasive status from genome scans. However, when considering broader patterns of adaptation to specific environmental variables through gGO analyses, we find that D. suzukii populations likely faced only limited adaptive challenges across their major invasion range, while certain uninvaded regions still remain at high risk of future invasion. Our study offers significant insights into D. suzukii adaptation and provides a practical population genomics framework to predict biological invasions, applicable to various species.

Adaptation of the Cyst Nematode Globodera pallida to the Colinear Potato Resistant QTLs GpaV vrn and GpaV spl Involved Distinct Genomic Regions and Absence of Cross‐Virulence - Océane Lechevalier; Magali Esquibet; Mathieu Gautier; Rachel Fourdin; Eric Grenier; Sylvain Fournet; Josselin Montarry (Molecular Ecology, 2025)
The use of alternative methods to control cyst nematode populations has accelerated since the ban of chemical nematicides in Europe. The resistant QTL GpaV vrn , derived from the wild species Solanum vernei , is widely present in resistant European potato cultivars and provides strong protection against Globodera pallida populations although a risk of resistance breakdown has already been demonstrated in both experimental evolution studies and field populations. The wild relative S. sparsipilum , harbouring the resistant QTL GpaV spl , would be an interesting alternative source of resistance to control virulent G. pallida . The goal of the present study was to understand the genomics of adaptation of the nematode to these two colinear resistant QTLs. Starting with two natural populations, an experimental evolution approach allowed, after 10 generations on resistant potato genotypes, selecting independent nematode lineages adapted to each QTL. These virulent lineages were analysed through a combination of phenotyping and genome scans approaches. Phenotyping enabled the quantification of virulence levels and confirmed resistance breakdowns. Pool‐Seq whole genome sequencing followed by genome scan analyses identified genomic regions under selection, potentially involved in the adaptive mechanisms to each resistance factor. Candidate genes within these regions provided insights into the genetic basis of adaptation, revealing effectors known to suppress plant immunity. As genome scans highlighted distinct genomic regions for the adaptation to both resistant factors, we were able to predict and phenotypically confirm the absence of cross‐virulence between nematode lineages evolving on GpaV vrn and GpaV spl . These findings have significant implications for the design of effective and sustainable resistance management strategies.

Performance of carbon and nitrogen removal in a system combining an aerobic trickling filter followed by two stages of vertical flow treatment wetland - Kevin Maciejewski; Mathieu Gautier; Boram Kim; Philippe Michel; Pascal Molle; Remy Gourdon (Ecological Engineering, 2024)

pH control on organic and organo-mineral colloids carrying major and trace elements in leachates of wetland sludge deposits - Camille Banc; Mathieu Gautier; Denise Blanc-Biscarat; Maria Lupsea-Toader; Rémi Marsac; Rémy Gourdon (Chemical Engineering Journal, 2023)

Monitoring of lamotrigine concentrations in five breastfed newborns - Marie-Andrée Thompson-Bos; Inge Harrewijn; Olivier Mathieu; Sophie Gautier; Cosette Le Souder (Neurotoxicology and Teratology, 2023)

Multiscale processes controlling niobium mobility during supergene weathering - Quentin Bollaert; Mathieu Chassé; Thierry Allard; Alexandra Courtin; Laurence Galoisy; Gautier Landrot; Cécile Quantin; Delphine Vantelon; Georges Calas (Geochimica et Cosmochimica Acta, 2023)

Olive mill solid waste gasification in a pilot-scale downdraft gasifier with three-stage air supply: performance, mass-energy balance and fate of inorganic elements - Gaëlle Ducom; Jean-Philippe Tagutchou; Mathieu Gautier; Carole Gaignaire; Jacques Méhu; Rémy Gourdon (Fuel, 2023)

Temperature, rainfall and wind variables underlie environmental adaptation in natural populations of Drosophila melanogaster - María Bogaerts‐Márquez; Sara Guirao‐Rico; Mathieu Gautier; Josefa González (Molecular Ecology, 2021)
While several studies in a diverse set of species have shed light on the genes underlying adaptation, our knowledge on the selective pressures that explain the observed patterns lags behind. Drosophila melanogaster is a valuable organism to study environmental adaptation because this species originated in Southern Africa and has recently expanded worldwide, and also because it has a functionally well‐annotated genome. In this study, we aimed to decipher which environmental variables are relevant for adaptation of D . melanogaster natural populations in Europe and North America. We analysed 36 whole‐genome pool‐seq samples of D . melanogaster natural populations collected in 20 European and 11 North American locations. We used the BayPass software to identify single nucleotide polymorphisms (SNPs) and transposable elements (TEs) showing signature of adaptive differentiation across populations, as well as significant associations with 59 environmental variables related to temperature, rainfall, evaporation, solar radiation, wind, daylight hours, and soil type. We found that in addition to temperature and rainfall, wind related variables are also relevant for D . melanogaster environmental adaptation. Interestingly, 23%–51% of the genes that showed significant associations with environmental variables were not found overly differentiated across populations. In addition to SNPs, we also identified 10 reference transposable element insertions associated with environmental variables. Our results showed that genome‐environment association analysis can identify adaptive genetic variants that are undetected by population differentiation analysis while also allowing the identification of candidate environmental drivers of adaptation.

Cadmium exposure enhances cell migration and invasion through modulated TRPM7 channel expression - Alison Vanlaeys; Grégory Fouquet; Philippe Kischel; Frédéric Hague; Sylvie Pasco-Brassart; Thibaut Lefebvre; Pierre Rybarczyk; Isabelle Dhennin-Duthille; Bertrand Brassart; Halima Ouadid-Ahidouch; Mathieu Gautier (Archives of Toxicology, 2020)
Cadmium is a xenobiotic involved in neoplastic transformation. Cadmium enters the cells through divalent cation transporters including the Transient Receptor Potential Melastatin-related 7 (TRPM7) which is known to be involved in cancer cell fate. This work aimed to study the role of TRPM7 in neoplastic transformation induced by cadmium exposure in non-cancer epithelial cells. Non-cancer epithelial cells were chronically exposed to low-dose of cadmium. TRPM7 expression and function were studied by Western-Blot, Patch-Clamp and calcium and magnesium imaging. Finally, cell migration and invasion were studied by Boyden chamber assays. Chronic cadmium exposure induced TRPM7 overexpression and increased the membrane currents ( P P P P P

A genomic map of climate adaptation in Mediterranean cattle breeds - Laurence Flori; Katayoun Moazami‐Goudarzi; Véronique Alary; Abdelillah Araba; Ismaïl Boujenane; Nadjet Boushaba; François Casabianca; Sara Casu; Roberta Ciampolini; Armelle Coeur D'Acier; Corinne Coquelle; Juan‐Vicente Delgado; et al. (Molecular Ecology, 2019)
Domestic species such as cattle ( Bos taurus taurus and B. t. indicus ) represent attractive biological models to characterize the genetic basis of short‐term evolutionary response to climate pressure induced by their post‐domestication history. Here, using newly generated dense SNP genotyping data, we assessed the structuring of genetic diversity of 21 autochtonous cattle breeds from the whole Mediterranean basin and performed genome‐wide association analyses with covariables discriminating the different Mediterranean climate subtypes. This provided insights into both the demographic and adaptive histories of Mediterranean cattle. In particular, a detailed functional annotation of genes surrounding variants associated with climate variations highlighted several biological functions involved in Mediterranean climate adaptation such as thermotolerance, UV protection, pathogen resistance or metabolism with strong candidate genes identified (e.g., NDUFB3 , FBN1 , METTL3 , LEF1 , ANTXR2 and TCF7 ). Accordingly, our results suggest that main selective pressures affecting cattle in Mediterranean area may have been related to variation in heat and UV exposure, in food resources availability and in exposure to pathogens, such as anthrax bacteria ( Bacillus anthracis ). Furthermore, the observed contribution of the three main bovine ancestries (indicine, European and African taurine) in these different populations suggested that adaptation to local climate conditions may have either relied on standing genomic variation of taurine origin, or adaptive introgression from indicine origin, depending on the local breed origins. Taken together, our results highlight the genetic uniqueness of local Mediterranean cattle breeds and strongly support conservation of these populations.

Identifying genomic hotspots of differentiation and candidate genes involved in the adaptive divergence of pea aphid host races - Pierre Nouhaud; Mathieu Gautier; Anaïs Gouin; Julie Jaquiéry; Jean Peccoud; Fabrice Legeai; Lucie Mieuzet; Carole M. Smadja; Claire Lemaitre; Renaud Vitalis; Jean‐Christophe Simon (Molecular Ecology, 2018)
Identifying the genomic bases of adaptation to novel environments is a long‐term objective in evolutionary biology. Because genetic differentiation is expected to increase between locally adapted populations at the genes targeted by selection, scanning the genome for elevated levels of differentiation is a first step towards deciphering the genomic architecture underlying adaptive divergence. The pea aphid Acyrthosiphon pisum is a model of choice to address this question, as it forms a large complex of plant‐specialized races and cryptic species, resulting from recent adaptive radiation. Here, we characterized genomewide polymorphisms in three pea aphid races specialized on alfalfa, clover and pea crops, respectively, which we sequenced in pools ( poolseq ). Using a model‐based approach that explicitly accounts for selection, we identified 392 genomic hotspots of differentiation spanning 47.3 Mb and 2,484 genes (respectively, 9.12% of the genome size and 8.10% of its genes). Most of these highly differentiated regions were located on the autosomes, and overall differentiation was weaker on the X chromosome. Within these hotspots, high levels of absolute divergence between races suggest that these regions experienced less gene flow than the rest of the genome, most likely by contributing to reproductive isolation. Moreover, population‐specific analyses showed evidence of selection in every host race, depending on the hotspot considered. These hotspots were significantly enriched for candidate gene categories that control host–plant selection and use. These genes encode 48 salivary proteins, 14 gustatory receptors, 10 odorant receptors, five P450 cytochromes and one chemosensory protein, which represent promising candidates for the genetic basis of host–plant specialization and ecological isolation in the pea aphid complex. Altogether, our findings open new research directions towards functional studies, for validating the role of these genes on adaptive phenotypes.

Interest of new alkylsulfonylhydrazide-type compound in the treatment of alcohol use disorders - Jérôme Jeanblanc; Erika Bourguet; Diana Sketriené; Céline Gonzalez; Gautier Moroy; Rémi Legastelois; Mathieu Létévé; Aurélie Trussardi-Régnier; Mickaël Naassila (Psychopharmacology, 2018)

Constitutive calcium entry and cancer: updated views and insights - Olivier Mignen; Bruno Constantin; Marie Potier-Cartereau; Aubin Penna; Mathieu Gautier; Maxime Guéguinou; Yves Renaudineau; Kenji F. Shoji; Romain Félix; Elsa Bayet; Paul Buscaglia; Marjolaine Debant; et al. (European Biophysics Journal, 2017)

Adaptive admixture in the W est A frican bovine hybrid zone: insight from the B orgou population - Laurence Flori; Sophie Thevenon; Guiguigbaza‐Kossigan Dayo; Marcel Senou; Souleymane Sylla; David Berthier; Katayoun Moazami‐Goudarzi; Mathieu Gautier (Molecular Ecology, 2014)
Understanding the adaptive response to environmental fluctuations represents a central issue in evolutionary biology. Population admixture between divergent ancestries has often been considered as an efficient short‐term adaptation strategy. Cattle populations from the West African Bos taurus × Bos indicus hybrid zone represent a valuable resource to characterize the effect of such adaptive admixture at the genome level. We here provide a detailed assessment of the global and local genome ancestries of the Borgou breed, one of the most representative cattle of this hybrid zone. We analysed a large data set consisting of 38 100 SNP s genotyped on 203 Borgou and 591 individuals representative of all the different cattle ancestries. At the global genomic level, we show that Borgou is a stabilized admixed breed whose origin ( c . 130 years ago) traces back to the great African rinderpest pandemic, several centuries after the last admixture events, the West African zebus originate from ( c . 500 years ago). To identify footprints of adaptive admixture, we combined the identification of signatures of selection and the functional annotation of the underlying genes using systems biology tools. The detection of the SILV coat coloration gene likely under artificial selection may be viewed as a validation of our approach. Overall, our results suggest that the long‐term presence of pathogens and the intermediate environmental conditions are the main acting selective pressures. Our analytical framework can be extended to other model or nonmodel species to understand the process that shapes the patterns of genetic variability in hybrid zones.

Estimation of population allele frequencies from next‐generation sequencing data: pool‐versus individual‐based genotyping - Mathieu Gautier; Julien Foucaud; Karim Gharbi; Timothée Cézard; Maxime Galan; Anne Loiseau; Marian Thomson; Pierre Pudlo; Carole Kerdelhué; Arnaud Estoup (Molecular Ecology, 2013)
Molecular markers produced by next‐generation sequencing ( NGS ) technologies are revolutionizing genetic research. However, the costs of analysing large numbers of individual genomes remain prohibitive for most population genetics studies. Here, we present results based on mathematical derivations showing that, under many realistic experimental designs, NGS of DNA pools from diploid individuals allows to estimate the allele frequencies at single nucleotide polymorphisms ( SNP s) with at least the same accuracy as individual‐based analyses, for considerably lower library construction and sequencing efforts. These findings remain true when taking into account the possibility of substantially unequal contributions of each individual to the final pool of sequence reads. We propose the intuitive notion of effective pool size to account for unequal pooling and derive a Bayesian hierarchical model to estimate this parameter directly from the data. We provide a user‐friendly application assessing the accuracy of allele frequency estimation from both pool‐ and individual‐based NGS population data under various sampling, sequencing depth and experimental error designs. We illustrate our findings with theoretical examples and real data sets corresponding to SNP loci obtained using restriction site–associated DNA ( RAD ) sequencing in pool‐ and individual‐based experiments carried out on the same population of the pine processionary moth ( Thaumetopoea pityocampa) . NGS of DNA pools might not be optimal for all types of studies but provides a cost‐effective approach for estimating allele frequencies for very large numbers of SNP s. It thus allows comparison of genome‐wide patterns of genetic variation for large numbers of individuals in multiple populations.

The effect of RAD allele dropout on the estimation of genetic variation within and between populations - Mathieu Gautier; Karim Gharbi; Timothee Cezard; Julien Foucaud; Carole Kerdelhué; Pierre Pudlo; Jean‐Marie Cornuet; Arnaud Estoup (Molecular Ecology, 2013)
Inexpensive short‐read sequencing technologies applied to reduced representation genomes is revolutionizing genetic research, especially population genetics analysis, by allowing the genotyping of massive numbers of single‐nucleotide polymorphisms ( SNP ) for large numbers of individuals and populations. Restriction site–associated DNA ( RAD ) sequencing is a recent technique based on the characterization of genomic regions flanking restriction sites. One of its potential drawbacks is the presence of polymorphism within the restriction site, which makes it impossible to observe the associated SNP allele (i.e. allele dropout, ADO ). To investigate the effect of ADO on genetic variation estimated from RAD markers, we first mathematically derived measures of the effect of ADO on allele frequencies as a function of different parameters within a single population. We then used RAD data sets simulated using a coalescence model to investigate the magnitude of biases induced by ADO on the estimation of expected heterozygosity and F ST under a simple demographic model of divergence between two populations. We found that ADO tends to overestimate genetic variation both within and between populations. Assuming a mutation rate per nucleotide between 10 −9 and 10 −8 , this bias remained low for most studied combinations of divergence time and effective population size, except for large effective population sizes. Averaging F ST values over multiple SNP s, for example, by sliding window analysis, did not correct ADO biases. We briefly discuss possible solutions to filter the most problematic cases of ADO using read coverage to detect markers with a large excess of null alleles.

Mineralogical study and leaching behavior of a stabilized harbor sediment with hydraulic binder - Vincent Chatain; Mostafa Benzaazoua; Marie Loustau Cazalet; Hassan Bouzahzah; Cécile Delolme; Mathieu Gautier; Denise Blanc; Christine de Brauer (Environmental Science and Pollution Research, 2013)

Adaptative modifications of right coronary myocytes voltage-gated K+ currents in rat with hypoxic pulmonary hypertension - Jean-Marc Hyvelin; Mathieu Gautier; Marie-Christine Lemaire; Pierre Bonnet; Véronique Eder (Pflügers Archiv - European Journal of Physiology, 2009)

Comparative gene mapping in cattle, Indian muntjac, and Chinese muntjac by fluorescence in situ hybridization - Andrea E. Murmann; Antoaneta Mincheva; Markus O. Scheuermann; Mathieu Gautier; Fentang Yang; Johannes Buitkamp; Pamela L. Strissel; Reiner Strick; Janet D. Rowley; Peter Lichter (Genetica, 2008)

A comprehensive radiation hybrid map of bovine Chromosome 26 (BTA26): comparative chromosomal organization between HSA10q and BTA26 and BTA28 - Mathieu Gautier; Hlne Hayes; Andr Eggen (Mammalian Genome, 2003)

A bovine whole-genome radiation hybrid panel and outline map - John L. Williams; André Eggen; Luca Ferretti; Christine J. Farr; Mathieu Gautier; Giuseppe Amati; Glynn Ball; Tiziana Caramorr; Ricky Critcher; Sandro Costa; Patrick Hextall; David Hills; et al. (Mammalian Genome, 2002)

An extensive and comprehensive radiation hybrid map of bovine Chromosome 15: comparison with human Chromosome 11 - Mathieu Gautier; Hélène Hayes; André Eggen (Mammalian Genome, 2002)